Cultivating Investment Awareness From an Early Age for High School Students at Raudhatul Ulum Sakatiga Islamic Boarding School, Ogan Ilir Regency - Khairani Putri Agustin; Muhammad Nazhif Kurdiawan Riza Utama; Fazila Maharani; Rina Tjandrakirana DP; Alditya Aris Rinandy (PT. Altaf Publishing Corp, 2025)
This community service activity aims to address the low understanding of investment and financial management among Islamic boarding school students as part of efforts to strengthen financial literacy from an early age. The program was carried out at Raudhatul Ulum Islamic Boarding School Integrated High School in Sakatiga, Ogan Ilir Regency, involving 40 students. The activity included interactive lectures, discussions, simulations, and practical mentoring over three days. The results showed that participants were able to understand the basic concepts of financial management, recognize various forms of simple investments, and demonstrate wiser attitudes toward managing their pocket money. This activity is expected to foster a culture of financial literacy among students and serve as an initial step in developing a smart, independent, and future-oriented young generation.